Tourism Sustainable Development Factor: A Bibliometric Analysis - Adiyanti, Assyifa Shafia; Widodo, Wahyu Indro; Disma, Fatimatuz Zahra; Firdaus, M. Surya Maulana; Ariyanto, Ariyanto; Nawing, Aditya (Journal of Information Systems Research and Practice, 2024)
Tourism has a significant impact on economic, environmental, and social aspects, hence the growth of the tourism industry is crucial in supporting sustainable development. This study analyzes the evolution of the concept of sustainable tourism using a bibliometric approach to 1858 research documents (2013–2023). The study uses bibliometric analysis to identify key tourism-related trends and issues as factors of sustainable development, including publication trends, author collaborations, and core journal sources. The growth of scientific publications reached 17.81% per year, focusing on the third Global Tourism Code of Conduct (GCET) Principles. The results of the analysis show thematic evolutionary trends, providing practical implications for responsible tourism management. The identification of core journals and the distribution of scientific production provide a holistic view of the global contribution to sustainable tourism development. This research provides an in-depth understanding for decision makers and practitioners in designing sustainable tourism policies in the future.